Issues of Writing Skills: Case Study of Indonesian Errors by Foreign Speakers from Timor Leste - Mayrita, Hastari; Abror, Muchlas (JOLLT Journal of Languages and Language Teaching, 2024)
There is a pressing need for professional Indonesian language teachers to enhance the learning experience for foreign speakers. This study focuses on examining language errors in BIPA (Indonesian for Foreign Speakers) learners’ essay writing, particularly in terms of punctuation placement, sentence structure, word choice, and the factors contributing to these errors. A qualitative method with a case study approach was employed, utilizing data collection techniques such as document analysis and Voice Note (VN) recordings via WhatsApp. The primary data sources included essays from BIPA students in Timor Leste and voice recordings of BIPA teachers in Timor Leste. The study identified several language errors in the students’ essays, including improper use of punctuation, incorrect word choice, and ineffective sentence structure. The researchers also uncovered several factors causing these errors: language and cultural gaps, insufficient learning resources and teaching staff, and inadequacies in the curriculum and foreign language learning policies. The implications of the research findings for BIPA learning are significant. To improve learning outcomes, it is essential to make learning resources more engaging and accessible. Additionally, addressing the gap between the targeted curriculum and student needs can be achieved by regularly evaluating and adjusting the language learning curriculum. Providing training to teachers and facilitating educators with a strong background in Indonesian language education are crucial steps to help BIPA students overcome their learning difficulties. These measures will contribute to a more effective and supportive learning environment for BIPA students.